Measurement invariance, validity, reliability, and factor structure examination of the creativity nurturing behaviour scale for teachers: comparisons across gender in thirteen countries - Sharma, Ekta; Sharma, Sandeep; Al-Qudah, Mohammed Amin Hamed; Yildiz, Canan; Adom, Dickson; Ferdinand, Debra; Mahmoud Hamad, Zaina Mustafa; Stavrianoudaki, Alexandra; Afhami, Reza (Creativity Studies, 2023)
Creativity is fundamental to the overall progress of humanity and hence identified as a key competence required for being successful in the 21st century. Teaching that nurtures creativity helps not only to unfold children’s creative potential but also to enhance the effectiveness of teaching. The essential step in helping teachers to learn the principles of creativity nurturing pedagogy is to measure creativity nurturing behaviour for teachers and develop it through training. Assessment of teachers’ ability to nurture creativity is much needed. In this research we measured the creativity nurturing behaviour of 2006 teachers from various countries across global with creativity nurturing behaviour scale for teachers and analyzed the four-factor model’s reliability, validity and measurement invariance across gender and countries. The following values were obtained: Cronbach’s alpha (0.75, 0.70, 0.72, 0.79), composite reliability (0.76, 0.72, 0.701, 0.784), configural invariance (comparative fit index: 0.913, root mean square error of approximation: 0.063 and standardized root mean square residual: 0.662), metric invariance (obtained value in comparative fit index: 0.912, root mean square error of approximation: 0.061 and standardized root mean square residual: 0.52) and scalar invariance (obtained value in comparative fit index: 0.909, root mean square error of approximation: 0.064 and standardized root mean square residual: 0.7). The results of the study show that creativity nurturing behaviour scale for teachers is a valid and reliable scale which is invariant across gender and countries. Hence, the scale can be administered to measure the creativity nurturing behaviour of teachers and its results can be employed to identify the developmental needs of teachers to foster creativity in the classroom. This first scale for teachers is translated into Hindi, Arabic, Spanish, English, Turkish, and Persian.